What makes a high performance organization five validated factors of competitive advantage that apply worldwide - De Waal, André (Global Professional Publishing Ltd., 2012)
"In his book André de Waal gives many real-life examples from a variety of sectors including finance, retail, industry, ICT, high education and government, all illustrating the successful workings of the HPO framework in organizations worldwide. Also included are many interviews with HPO leaders at Microsoft, SABMiller, Svenska Handelsbanken, HP, Tata Steel, Umpqua Bank, Unilever and KLM Royal Dutch Airlines"--Jacket, page [2].